(untitled) (Itinerarios Educativos, 2020)
This article deals with some aspects of the new articulated area for secondary level: the Seminar of Social Sciences. Its innovative potential and some tensions detected between curricular design and its implementation are addressed through an experience with students attending the second year of Juan Marcos Secondary School in the city of Santa Fe, Argentina, who worked on case studies about the Shoah, the process of persecution and extermination suffered by the European Jewish people under the national socialist regime of the German Third Reich before and during the Second World War. The curricular proposal was defined according to the curriculum designed by the Provincial Ministry of Education in relation to the Seminar, the decisions of incorporating subjects related to the Holocaust in our educational jurisdiction, and the teaching training course on the Shoah offered by the provincial government. The experience brought about high motivation in various ways, which we tried to relate to the Seminar area that was still being constructed.